Influence of School Principal Leadership, Work Motivation, and Work Discipline on Teacher Performance in the Bangun Mulia Vocational School - Sabaruddin Sinulingga; beti nurbaiti; Zian Fachrian (STIE Malangkucecwara, 2023)
This research was conducted with the aim to determine the effect of Principal Leadership, Work Discipline and Work Motivation on Teacher Performance at the Vocational School Bangun Mulia Foundation. This research is a type of quantitative research that will examine the effect of variables, namely exogenous and endogenous variables by testing hypotheses. The sample used in this study was 91 respondents. The author uses a quantitative method using Structural Equation Modeling (SEM) with the help of Lisrel 8.8 software. and Annova. (t value > 1.96) and the primary data is obtained from questionnaires whose measurements use a Likert scale that is tested for validity and reliability. The results of the study based on the validity and reliability test showed that the data was valid and reliable. Based on the t test and F test shows that the leadership of the school principal and Work Discipline, simultaneously influences the performance of teachers in SMK Bangun Mulia Foundation, while the most significant is the Principal's Leadership on Teacher Performance.